2005
DOI: 10.1227/01.neu.0000180811.56157.e1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Apoptosis-related Gene, PDCD10, Cause Cerebral Cavernous Malformation 3

Abstract: Our data establish PDCD10 as the gene responsible for CCM in families linking to the CCM3 locus. The discovery of the third gene involved in inherited forms of CCM, after KRIT1 and Malcavernin, is an important step toward dissecting the molecular pathophysiology of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 29 publications
0
64
0
1
Order By: Relevance
“…8) and was identified previously as an interactor for the GCKIII proteins (9,10). CCMs are vascular lesions of the brain characterized by enlarged capillaries that lack structural integrity and that form caverns that tend to bleed, leading to symptoms ranging from headaches and dizziness to severe strokes and death (reviewed in Ref.…”
Section: Pp2amentioning
confidence: 99%
“…8) and was identified previously as an interactor for the GCKIII proteins (9,10). CCMs are vascular lesions of the brain characterized by enlarged capillaries that lack structural integrity and that form caverns that tend to bleed, leading to symptoms ranging from headaches and dizziness to severe strokes and death (reviewed in Ref.…”
Section: Pp2amentioning
confidence: 99%
“…A majority of mutations in CCM genes result in truncations of their protein products, CCM1 (Krev/Rap1 Interacting Trapped 1; KRIT1) (3, 4), CCM2 (malcavernin, MGC4607, osmosensing scaffold for mitogen-activated protein kinase kinase kinase-3; OSM) (5, 6), and CCM3 (programmed cell death 10; PDCD10, TF-1 cell apoptosis-related protein 15; TFAR15) (7,8). These mutations are inherited in an autosomal dominant fashion (9) with acquisition of CCM lesions hypothesized to be due to a two-hit mechanism (10 -12).…”
Section: Cerebral Cavernous Malformation (Ccm)mentioning
confidence: 99%
“…Familial CCMs are inherited in an autosomal dominant pattern, constitute up to 50% of CCM cases, and have been found to be associated with loss-of-function mutations in 3 genes, KRIT1 (also known as CCM1) (1)(2)(3), CCM2 (MALCAVERNIN, OSM) (4,5), and PDCD10 (CCM3) (6,7). Genetic studies in zebrafish have demonstrated that loss of ccm1, ccm2, or the transmembrane receptor heart of glass (heg) results in embryonic cardiovascular phenotypes characterized by a large, thin-walled heart and defective branchial arch artery development that prevents blood circulation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%